Enrichment of neutrophils and monocytes from the liver following either oral or intravenous Listeria monocytogenes infection - Pitts, Michelle G. (Curr Protoc Immunol, 2020)
Listeria monocytogenes is a foodborne pathogen that causes serious, often deadly, systemic disease in susceptible individuals such as neonates and the elderly. These facultative intracellular bacteria have been an invaluable tool in immunology research for more than three decades. Intravenous (i.v.) injection is the most commonly used transmission route in mice, but oral models of infection have also been developed in recent years and these may be more appropriate for many studies. This unit includes detailed instructions for use of either foodborne or i.v. inoculation of mice and discusses the rationale for choosing either model. Additionally, a protocol is provided for enrichment of neutrophils and monocytes from the infected liver in a manner that allows for determination of bacterial burden while still providing sufficient cells for use in flow cytometric analysis or in vitro assays.